Diagnostic Approach to Gastroesophageal Reflux Disease: The Role of GERD Questionnaire and PPI Test - Ummu Habibah; Achmad Fauzi (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2015)
Gastroesophageal Reflux Disease (GERD), according to American College of Gastroenterology (ACG), is symptoms or mucosal damage produced by abnormal reflux of gastric contents into the esophagus. In most patients with GERD, showed no abnormalities in the endoscopic picture. This is what underlies the importance of a diagnostic tool in the form of assessment for the degree of severity of the disease based on symptoms, response to therapy and effect on the patients’ quality of life. This diagnostic tool is then formulated in the form of a questionnaire (GERD Questionnaire). Response to treatment with proton pump inhibitor (PPI) drugs is also often used to support the diagnosis of this disease.DIAMOND study is a large study which aim to assess the accuration of the questionnaire and use of PPI test. Diagnostic method with questionnaire modality and followed by PPI test have sensitivity and specificity value, which are relatively similar to the symptoms-based diagnoses performed by general practitioners or gastroenterologist, as well as when compared to endoscopy and esophageal pH monitoring. Although the diagnosis by methods of questionnaires and PPI test is not the most ideal test in term of accuracy, but these tests are not expensive, readily available and worked mainly on primary health care. These test methods are favored compared to other tests.